2016
DOI: 10.1007/s11064-016-1911-3
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes Grown in Alvetex® Three Dimensional Scaffolds Retain a Non-reactive Phenotype

Abstract: Protocols which permit the extraction of primary astrocytes from either embryonic or postnatal mice are well established however astrocytes in culture are different to those in the mature CNS. Three dimensional (3D) cultures, using a variety of scaffolds may enable better phenotypic properties to be developed in culture. We present data from embryonic (E15) and postnatal (P4) murine primary cortical astrocytes grown on coated coverslips or a 3D polystyrene scaffold, Alvetex. Growth of both embryonic and postna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 62 publications
(92 reference statements)
2
29
0
Order By: Relevance
“…Furthermore astrocyte morphology is notably different in such 3D cultures when compared with 2D monolayers. This is particularly interesting when the astrocyte morphology seen in 3D culture (extensive, intricate processes) was more consistent with astrocyte morphology in vivo than with that seen in comparator 2D monolayer cultures, as previously described [14]. However, given growing recognition of the 'quadpartite synapse' [12], investigations of microglia in 3D scaffolds such as Alvetex are warranted.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Furthermore astrocyte morphology is notably different in such 3D cultures when compared with 2D monolayers. This is particularly interesting when the astrocyte morphology seen in 3D culture (extensive, intricate processes) was more consistent with astrocyte morphology in vivo than with that seen in comparator 2D monolayer cultures, as previously described [14]. However, given growing recognition of the 'quadpartite synapse' [12], investigations of microglia in 3D scaffolds such as Alvetex are warranted.…”
Section: Discussionsupporting
confidence: 51%
“…While a variety of commercial and bespoke scaffolds which support 3D cell culture are now in use [11] and neuronal-glial cultures have previously been grown on Alvetex membranes [14], our results demonstrate for the first time that spontaneously active, functional networks can be formed and monitored using murine central nervous system cells grown within this substrate. Specifically, we show viable murine mixed neuronal-glial cultures grow in 3D within the Alvetex substrates.…”
Section: Discussionmentioning
confidence: 71%
“…For three‐dimensional (3D) transwell experiments, primary cortical astrocytes were seeded on Alvetex ® 6‐ and 12‐well hanging inserts (Reinnervate, Durham, UK) as previously described (Ugbode et al . ). The primary astrocyte cultures were of 95% purity.…”
Section: Methodsmentioning
confidence: 97%
“…As HMGEC cultured on ThinCert did not yield convincing results, we further tested Alvetex scaffolds allowing cells to proliferate three-dimensionally, thereby communicating more dynamically, 34 to differentiate in response to distinct stimuli 35,36 and to function in an appropriate microenvironment. 37,38 Histologic analysis demonstrated that HMGECs exhibited the same appearance regardless of their location within Alvetex.…”
Section: Discussionmentioning
confidence: 99%